Cultural hibrity on urban space: the São Paulo of Luiz Ruffato - Zamberlan, Lucas da Cunha (2015)
This article aims to reflect about the discursive mechanisms of the novel Eleserammuitoscavalos, by Luiz Ruffato, showing the sociocultural phenomenon of hybridity as a key element in the composition of urban space of São Paulo.In order to reach our goal, we suited the study to the following methodological parameters: a) accurate analysis of aesthetic resources manipulated by the author in order to understand how certain themes so relevant to debate the social weltgefuehl of Latin-America, are consolidated to framework of the novel; b) comprehension of hybridity as a key concept in the configuration of both interpersonal relationships between inhabitants of metropolis, and the organization of fragments, giving unity to the narrative; c) literary criticism from literature theory and sociology in attempt to promote dialogue of the spheres of knowledge that support this scientific research.To achieve our hypotheses, findings and questions, we constructed a theoretical framework that Canclini (2013), Calvino (2010), Bauman (2001), (2009), Canevacci (1996), Bakhtin (2012), Giddens (2008), Landowski (2002), among others. From analyzed constituents, we conclude that socio-cultural hybridity that compose the setting of large Latin American cities is consistent with experimentation of the novel forms, pointing a path where multiplicity and heterogeneity play a key role.